Analisis Implementasi Digitalisasi Sistem Akuntansi Keuangan Di Koperasi Kpn Tuah Sepakat Kabupaten Tanah Datar - Dilla Gustiana; Rahmaita . (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to analyze the implementation of the financial accounting system at the KPN Tuah Sepakat Cooperative located in Tanah Datar Regency. The main focus of this study is to evaluate the extent to which the financial accounting system implemented is in accordance with generally accepted accounting principles and cooperative regulations set by the government. The method used is a qualitative approach with data collection techniques through observation in-depth interviews, and documentation studies. The results of the study indicate that the KPN Tuah. Cooperative has implemented a fairly systematic manual-based financial accounting system, but there are still some weaknesses in recording, classifying, and reporting finances. Factors inhibiting optimal implementation include limited human resources who understand accounting principles and the lack of utilization of information technology. This study recommends increasing human resource capacity through training and adopting a digital-based accounting system to improve the efficiency and accuracy of cooperative financial reports.